The Culinary Writing of Plautina Nunes Horta: Mariana (MG), 19th and 20th Centuries - Magalhães, Sônia Maria de (Projeto História : Revista do Programa de Estudos Pós-Graduados de História, 2021)
This article analyzes the culinary recipe book of Mrs. Plautina Nunes Horta, who lives in the interior of Minas Gerais, which began to be written in 1896. It reveals the universe of a woman who achieved prominence in the social nucleus in which she lived through her homemade grocery stores. This type of domestic and private manuscript presents narratives of female personal experiences with no intention of publication, distinguishing itself by the free construction of the text and the absence of formal writing conventions. In this biographical act they endow the world around them with particular meanings, connected with their own lives, which in no way need to have any exceptional attribute to be worthy of being remembered.